2020
DOI: 10.1186/s40709-020-00119-0
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of cancer in vertebrates: a mini review

Abstract: Neoplasia is a multilevel condition caused by irregularities over the genome, which can lead to a fatal result. To fully understand this phenomenon, an evolutionary challenge has risen during the last decades, away from human limits, driving the scientific quest into the wild life. The study of wild vertebrate populations in their natural habitats has shown that cancer is rather prominent. Thus, the diversity of vertebrates reported with some form of neoplasia is quite scattered through a variety of habitats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 70 publications
(102 reference statements)
1
16
0
Order By: Relevance
“…Disruption of p53 protein function causes the occurrence of cancer cell features [ 12 ]. The presence of extra copies results in an effective DNA damage response through the hyperactive TP53 pathway ( Figure 3 a) [ 44 ].…”
Section: Cancer and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of p53 protein function causes the occurrence of cancer cell features [ 12 ]. The presence of extra copies results in an effective DNA damage response through the hyperactive TP53 pathway ( Figure 3 a) [ 44 ].…”
Section: Cancer and Evolutionmentioning
confidence: 99%
“…Similar changes have been identified in hypoxia-tolerant human tumors [ 13 , 49 ]. Interestingly, despite many studies, no cases of malignant neoplasm have been found in this species [ 44 ].…”
Section: Cancer and Evolutionmentioning
confidence: 99%
“…Antioxidant capacity is elevated and DNA-damage is reduced (Conde-Pérezprina et al, 2012) in long-lived (Desmodus rotundus) compared to short-lived species (Myotis velifer) and in torpid compared to active individuals (Sturnia lilium; Wilhelm Filho et al, 2007). Consistent with low cancer incidence (Kitsoulis et al, 2020), DNA repair and signaling pathways are maintained throughout the lifespan (Huang et al, 2019) and two long-lived species (M. myotis, M. lucifugus) possess additional copies of the tumor suppressor FBX031 (Seim et al, 2013). The genomes and transcriptomes published by Seim et al together with further finished and ongoing genome sequencing projects of the approximately 1300 living bat species provide a solid basis for future comparative studies (Jebb et al, 2020).…”
Section: Bats (Chiroptera)mentioning
confidence: 96%
“…This model predicts that regeneration-competent species will show higher rates of cancers such as glioblastoma and neuroblastoma-like tumors. In addition, regenerative competence might be expected to decrease with age, as the probability of tumor formation increases (Kitsoulis et al, 2020).…”
Section: Hypothesis 3: Loss Of Regenerative Competence Is An Adaptati...mentioning
confidence: 99%